2022
DOI: 10.1002/ecs2.4190
|View full text |Cite
|
Sign up to set email alerts
|

Implications of habitat‐driven survival and dispersal on recruitment in a spatially structured piping plover population

Abstract: Natal survival and dispersal have important consequences for populations through the movement of genes and individuals. Metapopulation theory predicts either balanced natal dispersal among regions or source-sink dynamics, which can dramatically change population structure. For species reliant on dynamic, early-successional habitats, availability and location of habitat will shift from year to year, requiring primiparous individuals to locate an appropriate breeding habitat. We estimated hatch-year survival to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…The Garrison Reach had high connectivity and a disproportionate effect on network connectivity during habitat loss simulations. Plovers may perceive sandbars on the Garrison Reach as high‐quality habitats, which has been suggested previously due to high nest and chick survival (Anteau et al, 2019; Shaffer et al, 2013; Swift, Anteau, Ellis, Ring, Sherfy, Toy, & Koons, 2021; Swift, Anteau, Ring, et al, 2020; Swift, Anteau, Roche, et al, 2020), high renest probability and success (Swift, Anteau, Ring, et al, 2020), high natal fidelity (Swift et al, 2022), and shorter dispersal distances (Swift, Anteau, Ellis, Ring, Sherfy, & Toy, 2021). High connectivity in the network graph also indicates that current management practices to provide an abundance of habitat on the riverine stretches of the Missouri River may be especially important (USFWS, 2018).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The Garrison Reach had high connectivity and a disproportionate effect on network connectivity during habitat loss simulations. Plovers may perceive sandbars on the Garrison Reach as high‐quality habitats, which has been suggested previously due to high nest and chick survival (Anteau et al, 2019; Shaffer et al, 2013; Swift, Anteau, Ellis, Ring, Sherfy, Toy, & Koons, 2021; Swift, Anteau, Ring, et al, 2020; Swift, Anteau, Roche, et al, 2020), high renest probability and success (Swift, Anteau, Ring, et al, 2020), high natal fidelity (Swift et al, 2022), and shorter dispersal distances (Swift, Anteau, Ellis, Ring, Sherfy, & Toy, 2021). High connectivity in the network graph also indicates that current management practices to provide an abundance of habitat on the riverine stretches of the Missouri River may be especially important (USFWS, 2018).…”
Section: Discussionmentioning
confidence: 92%
“…Adults were captured at the nest site with either a remote‐controlled walk‐in trap or bow net and banded with a U.S. Geological Survey (USGS) aluminum band, a unique combination of color bands, and a unique alpha‐numeric engraved flag. Individuals could have been previously marked prior to 2014 for other studies (Anteau et al, 2019; Shaffer et al, 2013) or marked as chicks and recruited into the breeding population (Swift et al, 2022). Adults were attributed to a nest by capturing individuals at the nest, observing known individuals return to incubate, or using video cameras briefly set up near the nest (Toy et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a post-hoc scenario where connectivity rates were increased to 0.13, extinction risk for the entire NGP population increased to 0.083above the proposed delisting criteria (McGowan et al, 2014;USFWS, 2016). A recent largescale empirical study resighting marked individuals found that dispersal between two spatially distinct breeding groups in the NGP was much higher than those initially simulated connectivity rates and was also unbalanced for both adult (U.S. Alkali Wetlands to Northern Rivers: 0.04, Northern Rivers to U.S. Alkali Wetlands: 0.17) and hatch-year (U.S. Alkali Wetlands to Northern Rivers: 0.33, Northern Rivers to U.S. Alkali Wetlands: 0.17) plovers (Swift et al, 2021a;Swift et al, 2022). This suggests that extinction risk for NGP plovers under high, unbalanced dispersal conditions may not meet the draft recovery criteria (USFWS, 2016) and needs to be reevaluated.…”
Section: Introductionmentioning
confidence: 80%
“…Piping plover habitats are widely distributed in the PPR, but nests are often concentrated within ‘hotspots’ (Ellis, Anteau, MacDonald, Swift, Ring, Toy, Sherfy, et al., 2023). This type of aggregation of nests across space is common for species that use patches of habitat distributed across large areas, for species exhibiting colonial or semi‐colonial nesting behaviours (Dardenne et al., 2013; Gibbs, 1991; Patrick, 2013), and where social cues or community interactions contribute to the spatial pattern of nests, in addition to habitat conditions (Cunningham et al., 2016; Samplonius & Both, 2017; Swift et al., 2017, 2023). Therefore, precision and bias will likely differ with varying aggregation and spatiotemporal autocorrelation of nest patterns and available habitats (Blanchard et al., 2008).…”
Section: Discussionmentioning
confidence: 99%